2011
DOI: 10.1126/scitranslmed.3003021
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Prevention of Urinary Tract Infection with Orally Active FimH Inhibitors

Abstract: Chronic and recurrent urinary tract infections pose a serious medical problem because there are few effective treatment options. Patients with chronic urinary tract infections are commonly treated with long-term prophylactic antibiotics that promote the development of antibiotic-resistant forms of uropathogenic Escherichia coli (UPEC), further complicating treatment. We developed small–molecular weight compounds termed mannosides that specifically inhibit the FimH type 1 pilus lectin of UPEC, which mediates ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
291
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(298 citation statements)
references
References 60 publications
3
291
0
4
Order By: Relevance
“…These and other considerations have generated an increased interest in the development of non-biocidal anti-infective strategies as alternatives to antibiotics, as these would be expected to show reduced tendency to provoke the appearance of resistant strains. [6][7][8][9][10][11][12][13] One such approach is the development of a † Electronic supplementary information (ESI) available. See DOI: 10.1039/ c4nr05906a ‡ These authors contributed equally to the work.…”
Section: Introductionmentioning
confidence: 99%
“…These and other considerations have generated an increased interest in the development of non-biocidal anti-infective strategies as alternatives to antibiotics, as these would be expected to show reduced tendency to provoke the appearance of resistant strains. [6][7][8][9][10][11][12][13] One such approach is the development of a † Electronic supplementary information (ESI) available. See DOI: 10.1039/ c4nr05906a ‡ These authors contributed equally to the work.…”
Section: Introductionmentioning
confidence: 99%
“…Also, methyl alpha-mannoside was reported to inhibit E. coli and Salmonella binding to glycoprotein CEACAM in vitro [78]. Also, selective FimH-binding mannosides have been indicated in preventing UTIs in a preclinical murine model [106]. In vitro studies have found that anti-CEACAM antibodies block the adhesion of M. catarrhalis, N. meningitidis and NTHi to airway epithelial cells [39,71,107].…”
Section: Inhibiting Specific Bacterial Adhesin-host Receptor Interactmentioning
confidence: 99%
“…α-d-Mannopyranosides tested in the UTI mouse model. Methyl and n-heptyl α-dmannopyranosides 1a and 1b, [7][8][9] biphenyl α-d-mannopyranoside 2a and 2b, [9] diamidobiphenyl α-d-mannopyranoside 3a and 3b [10] and monoamidobiphenyl α-d-mannopyranoside 4.…”
Section: Upia Type 1pilimentioning
confidence: 99%
“…1. Timeline of the major steps of the development of antibiotics (top [4] ) and the FimH antiadhesion therapy for the treatment of UTI (bottom [5][6][7][8][9][10] ).…”
Section: Antibiotics and Resistance -The Microbiological Tw Insmentioning
confidence: 99%